Takeaway food consumption and depressive symptoms in Chinese university students: mediating effects of physical activity - Tan, Jianyu; Wang, Rui; Su, Zhewei; Kong, Yiting; Ran, Pan; Greenshaw, Andrew; Hong, Su; Zhang, Qi; Wang, Wo; Ai, Ming; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundThe consumption of takeaways is becoming increasingly prevalent. Despite this, the relationship between takeaway food consumption and depressive symptoms in Chinese populations has not been clarified. Furthermore, the factors that mediate the association between takeaway frequency and depressive symptoms are unknown.MethodsQuestionnaires were employed to collect data from 6,417 new students at Chongqing Medical University in the autumn of 2023, including sociodemographic information, takeaway frequency, physical activity levels (measured by the International Physical Activity Questionnaire Short Form), and depressive symptoms (measured by the Patient Health Questionnaire-9). Multiple linear regression and mediation analysis were performed. Multiple imputations were used to fill in missing data through sensitivity analyses.ResultsAmong 6417 participants, 2,606 (40.6%) students ordered takeaway at least once a week, with 235 (3.7%) of them ordering takeaway food every day. Takeaway frequency was significantly associated with depressive symptoms (β=0.034, P=0.006), and physical activity partially mediated this relationship (95% bootstrap confidence interval=0.0024, 0.0371).ConclusionsThe study highlights the negative relationship between takeaway frequency and emotional well-being, emphasizing the need to focus on the emotional health of frequent takeaway food consumers. Moreover, our study suggests that increased physical activity may alleviate takeaway-induced mood-related outcomes.